Phytocenotic arrangement of the common hop in the south of western Siberia - M. M. Silantyeva; O. N. Mironenko; N. V. Ovcharova; I. G. Chukhina; Yu. R. Poltaratskaya; A. V. Nebylitsa; O. V. Bychkova; E. P. Myakisheva (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Common hop (Humulus lupulus L.) is actively used in brewing and has great potential for pharmaceutical and cosmetic industries because of its wide diversity of bioactive substances. Development of new high-yielding Russian cultivars requires studying the existing natural characteristics of the species, as well as its ecotopologic and phytocenotic arrangement in the south of Western Siberia, where its significant genetic resources are concentrated.Materials and methods. Plant explorations that resulted in 400 herbarium sheets and 275 geobotanical descriptions were conducted in 2023–2024 in Altai Territory, Novosibirsk, Kemerovo, Tyumen and Omsk Provinces, and Altai Republic, also covering the adjacent areas of Krasnoyarsk Territory, and Khakassia. The search for common hop thickets in remote and inaccessible locations was made with a DJI Mavic 3 Multispectral unmanned aircraft. Primary classification and ordination of plant communities took into account the composition, projective coverage, and permanence of plant species. Over 900 hop growth localities, both under cultivated and natural conditions, were marked on the digitized map of vegetation for the south of Western Siberia.Results. Over the southwest of Siberia, common hop presently occurs within various phytocenoses situated in the steppe and forest-steppe zones, and the southern taiga subzone of the forest zone, from low to medium mountains. Hop has a significant range of habitats, from undisturbed forest phytocenoses to urbanized areas. The cultivated part of its area was formed during Siberia’s colonization. There are 16 natural and 13 anthropogenic ecotopes where this species can be found. In the plant communities that incorporated common hop plants, 62 species of trees and shrubs were observed to serve as supports, the active core of the cenoflora consisted of 50 plant species, and 782 higher plant species were recorded in total.